Synthetic method of delta-phase perovskite crystal and delta-phase perovskite crystal prepared by method

Through a new process, organic anion precursor and metal ion precursor are added to the solvent, and after heating, anti-solvent input, multiple cleaning and filtration, the delta-phase perovskite crystals are finally dried to obtain high yield and high purity, which solves the problems of low yield and complex process in the prior art, and realizes the economical production of perovskite solar cells.

CN119630678APending Publication Date: 2025-03-14HANWHA SOLUTIONS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380057005.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-25
Filing Date
2023-05-17
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art has low yields, complex processes and high energy consumption when preparing high-purity delta-phase perovskite crystals, which limits the large-scale production and economicalization of perovskite solar cells.

Method used

A new process is adopted, including adding organic anion precursor and metal ion precursor to the solvent, and after heating, anti-solvent input, multiple cleanings and filtration, the delta-phase perovskite crystals are finally obtained through drying.

Benefits of technology

The high yield (up to 90%) and high purity (up to 99%) of delta-phase perovskite crystals are achieved, which reduces production costs and energy consumption, and promotes the large-scale production and economicalization of perovskite solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630678A_ABST
    Figure CN119630678A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a delta-phase perovskite crystal, in particular to a novel method for synthesizing the delta-phase perovskite crystal with high yield and the delta-phase perovskite crystal prepared by using the novel method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing delta-phase perovskite crystals with high yield and high purity and delta-phase perovskite crystals prepared by the method. Background Art

[0002] In order to solve the global environmental problems caused by the depletion of fossil energy and its use, research on renewable and clean alternative energy such as solar energy, wind power, and water power is being actively carried out.

[0003] Among them, the interest in solar cells that directly convert electricity from sunlight has greatly increased. Here, solar cells refer to cells that generate current and voltage by using the photovoltaic effect of generating electrons and holes by absorbing light energy from sunlight.

[0004] At present, it is possible to prepare solar cells based on np diode-type silicon (Si) single crystals with a light energy conversion efficiency greater than 20% for use in actual solar power generation, and there are also solar cells using compound semiconductors such as gallium arsenide (GaAs) with even better conversion efficiency. However, in order to achieve high efficiency, such solar cells based on inorganic semiconductors require raw materials purified to a very high purity, so the purification of raw materials consumes a lot of energy, and in the process of using raw materials to form single crystals or thin films, expensive process equipment is required, so there are limitations in reducing the production cost of solar cells, which has become a stumbling block for large-scale use.

[0005] Therefore, in order to produce solar cells at a low cost, it is necessary to significantly reduce the cost of raw materials or production processes used as the core of solar cells. As an alternative to inorganic semiconductor-based solar cells, perovskite solar cells that can be produced using low-cost raw materials and processes are being studied.

[0006] The general structural formula of perovskite structure is AMX 3 The structure has an anion located at the X position, a larger cation located at the A position, and a smaller cation located at the M position.

[0007] This perovskite compound has excellent electrical conductivity, charge mobility and optical properties, and has a wide range of applications. It has many characteristics including long life, high absorption wavelength spectrum due to small band gap and wide charge-carrier diffusion length. At the same time, it has the advantages of economical raw material prices, can be made into solutions, low process costs, and can be prepared through low-temperature processes. It has attracted much attention as a potential material for renewable energy applications. In particular, research on its use as a light absorber and as a perovskite solar cell continues.

[0008] In the preparation of ABX 3In the conventional synthesis method of perovskite crystals with the structure (A = monovalent organic cation, B = divalent metal cation, X = halogen ion), ABX is synthesized at high temperature in a solvent. 3 Then, AX and BX are obtained by filtering and drying. 2 , the synthesis yield is low, the mass productivity is poor, and when AX as a precursor for synthesis is synthesized, unnecessary by-products are produced, which has the limitation of low yield. Summary of the invention

[0009] Technical issues

[0010] The present invention is conceived to overcome the above problems and to provide a method for preparing a δ-phase perovskite composite material in a high yield and / or high purity by using a precursor different from the existing ones and a δ-phase perovskite composite material prepared by the method.

[0011] Solutions to the problem

[0012] In order to solve the above problems, the present invention relates to a method for preparing a δ-phase perovskite crystal, and a process is performed, which comprises: a first step, after adding a solvent into a reactor, adding an organic anion precursor represented by the following chemical formula 1 and a metal ion precursor represented by the following chemical formula 2 into the above solvent to dissolve them, and preparing a reaction solution; a second step, heating the above reaction solution to 20 to 110° C., and when the reaction solution turns yellow, adding an anti-solvent (anti solution) to obtain a solution including a precipitate; a third step, after removing the colorless solution from the solution including the precipitate of the second step, washing the precipitate for the first time with a bad solvent; a fourth step, washing the precipitate subjected to the first washing for the second time with an ether solvent and filtering it to obtain a filtrate; and a fifth step, by drying the above filtrate, obtaining a δ-phase perovskite crystal represented by the following chemical formula 3.

[0013] Chemical formula 1

[0014] AX

[0015] Chemical formula 2

[0016] BX 2

[0017] Chemical formula 3

[0018] ABX 3

[0019] In the above chemical formula 1 and chemical formula 3, A is formamidinium (FA), methylammonium (MA), FA x MA (1-x)(0 < X < 1) or N(R 1 ) 4 + , R 1 is a straight-chain alkyl group with 1 to 5 carbon atoms, a branched alkyl group with 3 to 5 carbon atoms, a phenyl group, an alkylphenyl group or an alkoxyphenyl group. In the above Chemical Formula 2 and Chemical Formula 3, B is Fe 2+ , Co 2+ , Ni 2+ , Cu 2+ , Sn 2+ , Pb 2+ , Bi 2+ , Ge 2+ , Ti 2+ , Eu 2+ or Zr 2+ , X is I - , Cl - or Br - .

[0020] As a preferred embodiment of the present invention, the solvent in the first step may include one or more selected from γ-butyrolactone, γ-valerolactone, α-angelica lactone, α-methylene-γ-butyrolactone, α-hydroxy-γ-butyrolactone, and ε-caprolactone.

[0021] As a preferred embodiment of the present invention, in the first step, the above reaction solution can include the above organic anion precursor and the above metal ion precursor in a molar ratio of 0.8 to 1.2:1.

[0022] As a preferred embodiment of the present invention, the above anti-solvent may include one or more selected from chlorobenzene, toluene, and xylene.

[0023] As a preferred embodiment of the present invention, the above poor solvent may include a nitrile-based solvent containing one or more selected from acetonitrile, propionitrile, and aminopropionitrile.

[0024] As a preferred embodiment of the present invention, the above-mentioned ether-based solvent may include one or more selected from diethyl ether, methyl tert-butyl ether, diisopropyl ether, and dibutyl ether.

[0025] As a preferred embodiment of the present invention, the δ-phase perovskite crystal obtained in the fifth step may have a yield of 75.00% or more and a purity of 99.00% or more, preferably a yield of 82.00% or more and a purity of 99.00% or more, and more preferably a yield of 90.00% or more and a purity of 99.00% or more.

[0026] Another object of the present invention is a δ-phase perovskite crystal prepared by the method as described above, and the above perovskite complex may be a perovskite crystal represented by the following Chemical Formula 3.

[0027] Chemical Formula 3

[0028] ABX 3

[0029] In the above Chemical Formula 3, A is formamidinium (FA), methylammonium (MA), FA x MA (1-x) (0 < X < 1) or N(R 1 ) 4 + , R 1 is a linear alkyl group having 1 to 5 carbon atoms, a branched alkyl group having 3 to 5 carbon atoms, a phenyl group, an alkylphenyl group, or an alkoxyphenyl group, B is Fe 2+ , Co 2+ , Ni 2+ , Cu 2+ , Sn 2+ , Pb 2+ , Bi 2+ , Ge 2+ , Ti 2+ , Eu 2+ or Zr 2+ , X is I - , Cl - or Br - .

[0030] Moreover, another object of the present invention is to provide a perovskite solar cell including the above perovskite crystal as a light absorption layer (or a photoactive layer).

[0031] Effects of the Invention

[0032] In the present invention, δ-phase perovskite crystals can be produced in large quantities with high yield and high purity by an economical method. Such δ-phase perovskite crystals of the present invention can be applied as raw materials in the electrical, electronic, or optical fields that require high electrical conductivity, charge mobility, and optical properties. As a preferred example, the above δ-phase perovskite crystals can be applied as a light absorption layer (photoactive layer) of a solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 A photograph showing a brief process of the synthesis process of the δ-phase perovskite crystal carried out in Example 1.

[0034] Figure 2 XRD measurement results of each of the δ-phase perovskite crystals synthesized in Examples 1 to 5 and Comparative Examples 1 to 3 in which an antisolvent was added by changing the temperature conditions.

[0035] Figure 3 A TGA analysis curve of the δ-phase perovskite crystal prepared in Example 2.

[0036] Figure 4 Performance test measurement results of the perovskite solar cells prepared in Preparation Examples 1 to 3. DETAILED DESCRIPTION

[0037] Hereinafter, the present invention will be described in more detail.

[0038] The present invention relates to a method for preparing a perovskite crystal represented by the following Chemical Formula 3.

[0039] Chemical Formula 3

[0040] ABX 3

[0041] In the above Chemical Formula 3, A is formamidinium (FA), methylammonium (MA), FA x MA (1-x) (0 < X < 1) or N(R 1 ) 4 + , preferably formamidinium (FA), methylammonium (MA) or FA x MA (1-x) (0 < X < 1), more preferably formamidinium (FA) or methylammonium (MA). And, the above R 1 is a linear alkyl group having 1 to 5 carbon atoms, a branched alkyl group having 3 to 5 carbon atoms, a phenyl group, an alkylphenyl group, or an alkoxyphenyl group. Preferably, the above R 1The straight-chain alkyl group is a linear alkyl group having 1 to 5 carbon atoms, and more preferably a linear alkyl group having 1 to 2 carbon atoms.

[0042] And, B in chemical formula 3 is Fe 2+ 、Co 2+ 、Ni 2+ , Cu 2+ Sn 2+ , Pb 2+ 、Bi 2+ ,Ge 2+ 、Ti 2+ 、Eu 2+ or Zr 2+ , preferably Cu 2+ Sn 2+ , Pb 2+ 、Bi 2+ ,Ge 2+ or Ti 2+ , more preferably Sn 2+ , Pb 2+ Or Bi 2+ .

[0043] And, X in Chemical Formula 3 is I - , Cl - or Br - , preferably 1 - or Cl - , more preferably 1 - .

[0044] Organic halides such as formamidinium iodide (FAI) are weaker than water, and purified organic halides are expensive. 3 ), if the organic halide is directly synthesized, it is not economical considering the low yield of the previous perovskite synthesis process.

[0045] The above-mentioned δ-phase perovskite crystal of the present invention can be synthesized by performing the following steps: First step, after introducing a solvent into a reactor, an organic anion precursor represented by the following Chemical Formula 1 and a metal ion precursor represented by the following Chemical Formula 2 are introduced into the above solvent and dissolved therein to prepare a reaction solution; Second step, the above reaction solution is heated to 20 to 110 °C, and when the reaction solution turns yellow, an anti-solvent is introduced to obtain a solution containing a precipitate; Third step, after removing the colorless solution from the solution containing the precipitate of the second step, the precipitate is first washed with a bad solvent; Fourth step, the precipitate washed for the first time is secondarily washed and filtered with an ether-based solvent to obtain a filtrate; and Fifth step, by drying the above filtrate, a δ-phase perovskite crystal represented by the following Chemical Formula 3 is obtained.

[0046] Chemical Formula 1

[0047] AX

[0048] In Chemical Formula 1, A is formamidinium (FA), methylammonium (MA), FA x MA (1-x) (0 < X < 1) or N(R 1 ) 4 + , preferably formamidinium (FA), methylammonium (MA) or FA x MA (1-x) (0 < X < 1), more preferably formamidinium (FA) or methylammonium (MA).

[0049] And, X in Chemical Formula 1 is I - , Cl - or Br - , preferably I - or Cl - , more preferably I - .

[0050] Chemical Formula 2

[0051] BX 2

[0052] B in Chemical Formula 2 is Fe 2+ , Co 2+ , Ni 2+ , Cu 2+ , Sn 2+ , Pb 2+ , Bi2+ ,Ge 2+ 、Ti 2+ 、Eu 2+ or Zr 2+ , preferably Cu 2 + Sn 2+ , Pb 2+ 、Bi 2+ ,Ge 2+ or Ti 2+ , more preferably Sn 2+ , Pb 2+ Or Bi 2+ And, X in Chemical Formula 2 is I - , Cl - or Br - , preferably 1 - or Cl - , more preferably 1 - .

[0053] The solvent of the first step may include at least one selected from γ-butyrolactone, γ-valerolactone, α-angelica lactone, α-methylene-γ-butyrolactone, α-hydroxy-γ-butyrolactone and ε-caprolactone, preferably, may include at least one selected from γ-butyrolactone, γ-valerolactone and α-angelica lactone, more preferably, may include at least one selected from γ-butyrolactone and γ-valerolactone.

[0054] Furthermore, the mixed solution of the first step may include the organic anion precursor and the metal ion precursor in a molar ratio of 0.8 to 1.2:1, preferably, in a molar ratio of 0.9 to 1.2:1, and more preferably, in a molar ratio of 0.95 to 1.1:1. At this time, when the molar ratio of the organic anion precursor is less than 0.8 or greater than 1.2 based on the metal ion precursor, there may be a problem of low perovskite crystal yield.

[0055] The first step can be performed at room temperature of 10-35°C, preferably 20-30°C. After the organic anion precursor and the metal ion precursor are added to the solvent and stirred for about 1-2 hours, they are completely dissolved in the solvent to form a transparent yellow reaction solution.

[0056] Then, in the above-mentioned second step, when the reaction solution in which the organic anion precursor and the above-mentioned metal ion precursor are dissolved in the first step is heated to 20-110°C, preferably 50-100°C, more preferably 50-80°C, and further preferably 55-70°C, the reaction solution becomes opaque or dark yellow.

[0057] Furthermore, when an anti-solvent is added dropwise, a yellow precipitate is generated, and the anti-solvent is added dropwise until the solution becomes colorless or transparent. At this time, the anti-solvent is preferably a benzene series, rather than an ether series such as diethyl ether, methyl tert-butyl ether, dimethyl ether, etc., whose yield is as low as about 30%.

[0058] At this time, when the above temperature is greater than 110°C, the yield of δ-phase perovskite crystals is too low due to the increase in α-phase perovskite crystals. When it is less than 20°C, too much anti-solvent is used, the reaction time becomes longer, and the yield of δ-phase perovskite crystals becomes lower, which is not economical.

[0059] Furthermore, the amount of the anti-solvent added is 200 to 400 volume ratios, preferably 230 to 370 volume ratios, and more preferably about 260 to 340 volume ratios, relative to 100 volume ratios of the solvent used in the first step.

[0060] Furthermore, the anti-solvent may include at least one selected from chlorobenzene, toluene and xylene, preferably, may include at least one selected from chlorobenzene and toluene, and more preferably, may include toluene.

[0061] Furthermore, the drying step for removing the reaction solvent remaining in the precipitate obtained in the second step before performing the following third step can be omitted.

[0062] Then, the third step is a process of using a bad solvent to wash the precipitate for the first time after removing the transparent and / or colorless solution. The above-mentioned bad solvent is preferably a nitrile solvent with a boiling point and high volatility, which can easily dissolve the organic anion precursor as the reaction residue but not the perovskite crystal as the reaction product, and has good miscibility with the solvent of the first step.

[0063] The nitrile solvent may be one or more selected from acetonitrile, propionitrile and aminopropionitrile. Preferably, one or more selected from acetonitrile and propionitrile may be used.

[0064] Furthermore, the first cleaning in the third step is repeatedly performed 1 to 3 times, preferably, repeatedly performed about 2 to 3 times.

[0065] Then, the fourth step is to perform a second washing with an ether solvent after removing the poor solvent used in the washing in the third step, and then filter to obtain the filtrate. The second washing is performed to remove the residual solvent used in the first step and the poor solvent used in the first washing.

[0066] The ether solvent used in the second cleaning may include one or more selected from diethyl ether, methyl t-butyl ether, diisopropyl ether and dibutyl ether, preferably, may include one or more selected from diethyl ether, methyl t-butyl ether and dibutyl ether, more preferably, may include one or more selected from diethyl ether and methyl tert-butyl ether.

[0067] And, the above-mentioned filtration may be performed by a conventional filtration method used in this field, and preferably, the filtration may be performed by performing reduced pressure filtration.

[0068] Furthermore, the washing and filtering in the fourth step are preferably repeated once or more, preferably 2 to 5 times, and more preferably about 3 to 5 times, which is preferable in terms of improving the purity of the δ-phase perovskite crystal.

[0069] Then, the fifth step is to dry the filtrate to obtain the yellow δ-phase perovskite crystals represented by the above chemical formula 3. The above drying can be performed by conventional methods used in this field. As a preferred example, the filtrate obtained in the fourth step can be stored in a vacuum oven for 12 to 36 hours to completely dry it.

[0070] When measured according to the following formula 1, the yield of the δ-phase perovskite crystal synthesized by the method of the present invention as described above may be 75.00% or more, preferably 82.00% or more, more preferably 90.00% or more, and even more preferably 93.0 to 99.0%.

[0071] Formula 1

[0072] Yield (%) = (weight of δ-phase perovskite crystals obtained) / (weight of organic anion precursor used in the reaction + weight of metal ion precursor used in the reaction) × 100%

[0073] The purity of the δ-phase perovskite crystal synthesized by the method of the present invention as described above can be 99.00% or more.

[0074] The δ-phase perovskite crystal prepared by the above method can be applied as a raw material for electrical, electronic or optical fields (solar cells, displays, lasers, sensors, etc.) that require high conductivity, charge mobility and optical properties. As a preferred example, the above-mentioned δ-phase perovskite crystal can be used as a precursor, and the light absorption layer with a target band gap can be more easily controlled by coating with a perovskite layer that can be used as a light absorption layer (photoactive layer) of a solar cell. Therefore, the band gap can be indirectly and effectively controlled.

[0075] A preferred example of a perovskite solar cell using the δ-phase perovskite crystal prepared by the method of the present invention as a light absorbing layer is as follows.

[0076] The above-mentioned perovskite solar cell can be a pin-structured perovskite solar cell, an inverse-structured perovskite solar cell, a tandem perovskite solar cell or a tandem silicon / perovskite heterojunction solar cell.

[0077] A preferred example of a perovskite solar cell is a solar cell comprising a stacked structure having a hole transport layer (HTL or hole transport layer), a perovskite light absorption layer, an electron transporting layer (ETL), a conductive barrier layer (Passivation layer) and a source electrode stacked in sequence.

[0078] Furthermore, when the solar cell is an inverse structure perovskite solar cell, the stacked body may be stacked on the drain electrode.

[0079] Furthermore, the above-mentioned inverse structure perovskite solar cell is composed of a group of conductive substrate, drain electrode, hole transport layer, light absorption layer, electron transfer layer and source electrode stacked in sequence, and the above-mentioned group can be formed by stacking a single layer or multiple layers.

[0080] As another preferred example, when the solar cell of the present invention is a tandem silicon / perovskite heterojunction solar cell, it can be in the form of a drain electrode, a silicon solar cell, a composite layer and the above-mentioned stacked body stacked in sequence.

[0081] If the method for preparing the above-mentioned stacked body constituting a perovskite solar cell is described in detail, the above-mentioned stacked body can be prepared by executing a process, which comprises: a first step of applying a coating agent for forming an electron transfer layer on the upper part of the perovskite light absorption layer of the stacked body comprising a hole transport layer and a perovskite light absorption layer to form an electron transfer layer; a second step of forming a passivation layer on the upper part of the above-mentioned electron transfer layer through a deposition process; and a third step of forming a source electrode on the upper part of the above-mentioned passivation layer.

[0082] The hole transport layer (HTL) may include inorganic and / or organic hole transport materials. The inorganic hole transport materials may include nickel oxide (NiO x )、CuSCN、CuCrO 2 and one or more of CuI.

[0083] The above-mentioned organic hole transporting material may include carbazole derivatives, polyaryl alkane derivatives, phenylenediamine derivatives, arylamine derivatives, amino-substituted chalcone derivatives, styryl anthracene derivatives, fluorene derivatives, hydrazone derivatives, distyrene derivatives, silazane derivatives, aromatic tertiary amine compounds, styrylamine compounds, aromatic dimethylimine compounds, porphyrin compounds, phthalocyanine compounds, polythiophene derivatives, polypyrrole derivatives, poly(p-phenylene vinylene) derivatives, pentacene, coumarin 6 (3-(2-benzothiazolyl)-7-(diethylamino)coumarin), zinc phthalocyanine (ZnPC), copper phthalocyanine (CuPC), titanium oxide phthalocyanine (TiOPC), etc. oxidephthalocyanine), Spiro-MeOTAD (2,2',7,7'-tetrakis(N,Np-dimethoxyphenylamino)-9,9'-spirobifluorene), Copper(II)1,2,3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluoro-29H,31H-phthalocyanine (F16CuPC, copper(II)1,2,3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluoro-29H,31H-phthalocyanine), Boron subphthalocyanine chloride (SubPc, boron subphthalocyanine chloride) and N3(cis-di(thiocyanato)-bis(2,2'-bipyridyl-4,4'-dicarboxylic acid)-ruthenium(II), poly[3-hexylthiophene] (P3HT), poly[2-methoxy-5-(3',7'-dimethyloctyloxy)]-1,4-phenylenevinylene (MDMO-PPV ...4-phenylene vinylene), poly[2-methoxy-5-(2"-ethylhexyloxy)-p-phenylenevinylene] (MEH-PPV), poly(3-octylthiophene) (P3OT), poly(octylthiophene) (POT), poly(3-decylthiophene) (P3DT), poly(3-dodecylthiophene) (P3DDT ... thiophene)), poly(p-phenylenevinylene) (PPV, poly(p-phenylenevinylene)), TFB (poly(9,9'-dioctylfluorene-co-N-(4-butylphenyl)diphenyl amine)), polyaniline, Spiro-MeOTAD ([2,22',7,77'-tetrakis(N,N-di-p-methoxyphenyl)-9,9,9'-spirocyclic fluoride]) amine)-9,9,9′-spirobifluorine])), CuSCN, CuI, poly[2,1,3-benzothiadiazole-4,7-diyl[4,4-bis(2-ethylhexyl-4H-cyclopenta[2,1-b:3,4-b']dithiophene-2,6-diyl]] (PCPDTBT, (Poly[2,1,3-benzothiadiazole-4,7-diyl[4,4-bis(2-ethylhexyl-4H-cyclopenta[2,1-b:3,4-b']dithiophene-2,6-diyl] ]), poly[(4,4′-bis(2-ethylhexyl)dithieno[3,2-b:2′,3′-d]silole)-2,6-diyl-alt-(2,1,3-benzothiadiazole)-4,7-diyl] (Si-PCPDTBT, (poly[(4,4′-bis(2-ethylhexyl)dithieno[3,2-b:2′,3′-d]silole)-2,6-diyl-alt-(2,1,3-benzothiadiazole)-4,7-diyl])), poly(4,8-diethylhexyl) (PBDTTPD, (poly(4,8-diethylhexyloxyl)), poly[2,7-(9-(2-ethylhexyl)-9-hexylfluorene)-alt-5,5-(4',7'-di-2-thienyl-2',1',3'-benzothiadiazole)] (PFDTBT, (poly[2,7-(9-(2-ethylhexyl)-9-hexyl-fluorene)-alt-5,5-(4',7'-di-2-thienyl-2',1',3'-benzothiadiazole)])), poly[2,7-.9,9-(dioctylfluorene)-alt-5,5-(4',7'-di-2-thienyl-2',1 ',3'-benzothiadiazole)](PFO-DBT,(poly[2,7-.9,9-(dioctyl-fluorene)-alt-5,5-(4',7'-di-2-thienyl-2',1',3'-benzothiadiazole)])),poly[(2,7-dioctylsilylfluorene)-2,7-diyl-alt-(4,7-bis(2-thienyl)-2,1,3-benzothiadiazole)-5,5′-diyl](PSiFDTBT,(poly[(2,7-dioctylsilafluorene)-2,7-diyl-alt-(4,7-bis(2-thi enyl)-2,1,3-benzothiadiazole)-5,5′-diyl])), poly[[9-(1-octylnonyl)-9H-carbazole-2,7-diyl]-2,5-thiophenediyl-2,1,3-benzothiadiazole-4,7-diyl-2,5-thiophenediyl] (PCDTBT, (Poly[[9-(1-octylnonyl)-9H-carbazole-2,7-diyl]-2,5-thiophenediyl-2,1,3-benzothiadiazole-4,7-diyl-2,5-thiophenediyl])), poly(9,9′-di Octylfluorene-co-bis(N,N′-(4,butylphenyl))bis(N,N′-phenyl-1,4-phenylene)diamine)(PFB,(poly(9,9′-dioctylfluorene-co-bis(N,N′-(4,butylphenyl))bis(N,N′-phenyl-1,4-phenylene)diamine)), poly(9,9′-dioctylfluorene-cobenzothiadiazole)(F8BT,(poly(9,9′-dioctylfluorene-cobenzothiadiazole)), poly(3,4-ethylenedioxythiophene))(PEDOT,(poly(3,4-ethylenedioxythiophene))), PEDOT:PSS poly(3,4-ethylenedioxythiophene)poly(styrenesulfonate)), polytriarylamine (PTAA, poly(triarylamine)), 2-PACz and / or MeO-2PACz. ,

[0084] The hole transport layer may be formed by coating or vacuum deposition. The coating may be formed by gravure coating, bar coating, printing, sputtering, spin coating, dip coating, or die coating.

[0085] Then, the light absorbing layer may include the delta-phase perovskite crystal represented by the chemical formula 3 as described above.

[0086] Then, the electron transport layer may include inorganic substances (e.g., metal oxides) and / or organic substances. The electron transport layer may be a flat metal oxide layer, a metal oxide layer with a concave-convex surface, a metal oxide layer having a composite structure of nanostructures (including metal oxide particles, nanowires and / or nanotubes) of the same or even different metal oxides formed on the surface of a thin film, or a porous metal oxide layer. Preferably, it may include a compact metal oxide layer and a porous metal oxide layer. As a preferred example, it may include TiO 2 SnO 2 , ZnO, etc. Also, the organic matter may include PCBM.

[0087] Furthermore, in the solar cell structure, the above-mentioned upper electrode (or source electrode) can be formed by coating or depositing one or more substances selected from Pt, Au, Ni, Cu, Ag, In, Ru, Pd, Rh, Ir, Os, C and conductive polymers.

[0088] Furthermore, the solar cell may further include a passivation layer between the light absorbing layer and the electron transporting layer.

[0089] Hereinafter, the present invention will be described in more detail by way of examples. However, the following examples do not limit the scope of the present invention and should be construed as helping to understand the present invention.

[0090] Example

[0091] Example 1: Synthesis of δ-phase perovskite crystals

[0092] After γ-butyrolactone as a lactone solvent was added to a conical flask, an organic anion precursor represented by the following chemical formula 1-1 and a metal ion precursor represented by the following chemical formula 2-1 were added and dissolved to prepare a transparent yellow reaction solution.

[0093] At this time, the mixing molar ratio of the organic anion precursor and the metal ion precursor is 1:1.

[0094] Then, the reaction solution was heated to about 25° C., and as the reaction solution became turbid and turned into an opaque yellow, toluene as an anti-solvent was added dropwise to the reaction solution, and stirring was performed.

[0095] Due to the addition of anti-solvent, a precipitate is generated, and toluene as an anti-solvent is added dropwise to the reaction solution to make it colorless (or transparent). At this time, the amount of anti-solvent added is about 3 times the volume ratio of the amount of γ-butyrolactone used.

[0096] Then, after removing the colorless (or transparent) reaction solution, acetonitrile as a bad solvent is added to the precipitate. After the bad solvent is added, the solvent becomes cloudy. The solvent is added until it becomes transparent, and the washing is repeated three times by discarding the solvent.

[0097] Then, the precipitate obtained by the first washing was washed with diethyl ether and filtered under reduced pressure to obtain a filtrate. The washing and filtering were repeated twice.

[0098] Then, the filtrate was stored in a vacuum oven for 24 hours to completely dry the filtrate, and a δ-phase perovskite crystal represented by the following Chemical Formula 3-1 was obtained (the yield was 91.2% and the purity was 99.90 to 99.95%).

[0099] In addition, the preparation process photos are shown in Figure 1 middle.

[0100] Chemical formula 1-1

[0101] AX

[0102] Chemical formula 2-1

[0103] BX 2

[0104] Chemical formula 3-1

[0105] ABX 3

[0106] In the above chemical formula 1-1 and chemical formula 3-1, A is formamidinium (FA), and in chemical formula 1-1, chemical formula 2-1 and chemical formula 3-1, B is Pb 2+ , X is I - .

[0107] Examples 2 to 3 and Comparative Examples 1 to 3

[0108] Perovskite crystals were prepared by the same method as in Example 1. When toluene as an anti-solvent was added to the reaction solution, the temperature of the reaction solution was changed to that shown in Table 1 below. Perovskite crystals were prepared respectively in Examples 2 to 3 and Comparative Examples 1 to 3.

[0109] Example 4

[0110] Perovskite crystals were prepared by the same method as in Example 2, except that chlorobenzene was used as an anti-solvent instead of toluene to prepare delta-phase perovskite crystals.

[0111] Example 5

[0112] Perovskite crystals were prepared by the same method as in Example 2, except that xylene was used as an anti-solvent instead of toluene to prepare δ-phase perovskite crystals.

[0113] Comparative Example 4

[0114] Perovskite crystals were prepared by the same method as in Example 1, except that diethyl ether, an ether solvent, was used as an antisolvent instead of toluene to prepare δ-phase perovskite crystals.

[0115] Table 1

[0116]

[0117] Experimental Example 1: XRD and TGA measurements

[0118] (1) XRD measurement

[0119] The XRD measurement results of the δ-phase perovskite crystals prepared in Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Figure 2 middle.

[0120] View Figure 2 It can be confirmed that the phase of the δ-phase perovskite crystal (powder) represented by Chemical Formula 3-1 obtained (synthesized) by changing the temperature of the solvent (γ-butyrolactone) in which the organic anion precursor and the metal ion precursor are dissolved changes.

[0121] Below 90°C, most of the synthesized perovskite crystals can be obtained in the δ phase, and in the range of about 110-150°C, the α phase and the δ phase are mixed. In addition, in the range of 150-180°C, it can be confirmed that most of the perovskite crystals are obtained in the α phase.

[0122] (2) TGA measurement

[0123] The TGA measurement results of the δ-phase perovskite crystal prepared in Example 2 are shown in Figure 3 In the figure, it can be confirmed that it is a high-purity δ-phase perovskite crystal.

[0124] Experimental Example 2: Yield Determination

[0125] The synthesis yields of the δ-phase perovskites prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were measured according to the following formula 1, and the results are shown in Table 2 below.

[0126] and, Figure 2 The XRD measurement results according to the temperature are shown in FIG.

[0127] Formula 1

[0128] δ-phase perovskite yield (%) = (weight of δ-phase perovskite crystals obtained) / (weight of organic anion precursor used in the reaction + weight of metal ion precursor used in the reaction) × 100%

[0129] Table 2

[0130]

[0131] According to Table 2, in Examples 1 to 5 in which the organic anion precursor and the metal ion precursor were synthesized at a temperature below 90° C., most of the δ-phase perovskites were obtained in the total perovskite yield.

[0132] Furthermore, in Example 4 using chlorobenzene as an anti-solvent and Example 5 using xylene, the total perovskite yield itself tends to be slightly lower than that in Example 2 using toluene as an anti-solvent.

[0133] Furthermore, compared to Example 1 synthesized at 25°C, the total perovskite yield of Example 2 synthesized at 60°C tends to be higher, and Example 3 synthesized at 90°C tends to have a relatively lower total perovskite yield than Example 2.

[0134] Moreover, in Comparative Examples 1 to 3 in which the organic anion precursor and the metal ion precursor were synthesized at 120 to 180°C, the total yield of perovskite was high, but Comparative Example 1 showed a greatly reduced yield of δ-phase perovskite compared to Example 3, and Comparative Examples 2 to 3 showed that most of the α-phase perovskite was obtained.

[0135] Furthermore, in Comparative Example 4 in which diethyl ether was used as an anti-solvent, compared with Example 2, the total yield of perovskite itself was low, and the yield of the δ phase was also relatively low.

[0136] Therefore, it can be confirmed that in terms of total perovskite yield and δ phase yield, productivity and economy, the temperature range of the organic anion precursor and the metal ion precursor is 40-90°C, and preferably, the optimal range is about 50-80°C.

[0137] Preparation Example 1: Preparation of perovskite solar cells

[0138] The δ-phase perovskite crystals, CsBr and PbBr prepared in Example 2 are 2 After being dissolved in dimethylformamide (DMF) and N-methyl-2-pyrrolidinone (NMP) to prepare a coating agent for forming a perovskite thin film, the coating agent was used to prepare (FAPbI 3 ) 0.8 (CsPbBr 3 ) 0.2 Opaque perovskite solar cell unit (Active area: 0.096 cm 2 Specifically, the structure of the opaque single element is NiO on an organic substrate deposited with ITO (100 nm). x (17nm), 2PACz (1nm), perovskite film (FAPbI 3 ) 0.8 (CsPbBr 3 ) 0.2 , 550nm), LiF (1nm), C60 (13nm), BCP (8nm), and Ag electrode (200nm).

[0139] Preparation Examples 2-3

[0140] The perovskite solar cell was prepared by the same method as in the above-mentioned Preparation Example 1, and the perovskite crystals prepared in Examples 4 and 5 were used instead of Example 2 to prepare solar cells, respectively, and Preparation Examples 2 and 3 were implemented respectively.

[0141] Comparative Preparation Example 1

[0142] Make FAI, PbI 2 , CsBr and PbBr 2After being dissolved in dimethylformamide (DMF) and N-methyl-2-pyrrolidinone (NMP) to prepare a coating agent (precursor solution) for forming a perovskite thin film, the precursor solution was used to prepare (FAPbI 3 ) 0.8 (CsPbBr 3 ) 0.2 The opaque perovskite solar cell unit (Active area: 0.096 cm 2 Specifically, the structure of the opaque single element is NiO on an organic substrate deposited with ITO (100 nm). x (17nm), 2PACz (1nm), perovskite film (FAPbI 3 ) 0.8 (CsPbBr 3 ) 0.2 , 550nm), LiF (1nm), C60 (13nm), BCP (8nm), and Ag electrode (200nm).

[0143] Experimental Example 2: Performance Measurement of Solar Cell Element

[0144] The current-voltage characteristics and efficiencies of the solar cells prepared in Preparation Examples 1 to 3 were measured, and the results are shown in Tables 3 and 4 below. Figure 4 middle.

[0145] Table 3

[0146]

[0147] See Table 3 above and Figure 4 It can be confirmed that Preparation Examples 1 to 3 all have relatively higher photoelectric conversion efficiency than Comparative Preparation Example 1. In particular, it can be confirmed that Preparation Example 1 has a photoelectric conversion efficiency that is about 2% higher than Comparative Preparation Example 1.

[0148] Through the above-mentioned embodiments and experimental examples, it can be confirmed that δ-phase perovskite crystals can be prepared with high yield while using less amount of chemicals than in the previous synthesis method, and it can be confirmed that when it is applied as a raw material for the light absorption layer, it can provide a perovskite solar cell with excellent efficiency.

Claims

1. A method for preparing a δ-phase perovskite crystal, performing the steps, wherein the preparation method is characterized in that: The process includes: In the first step, after a solvent is added into a reactor, an organic anion precursor represented by the following chemical formula 1 and a metal ion precursor represented by the following chemical formula 2 are added into the solvent to dissolve them, thereby preparing a reaction solution; The second step is to heat the reaction solution to 20-110° C., and when the reaction solution turns yellow, add an anti-solvent to obtain a solution including a precipitate; The third step is to remove the colorless solution from the solution including the precipitate in the second step, and then wash the precipitate for the first time with a poor solvent; The fourth step is to use an ether solvent to perform a second washing and filtering on the precipitate obtained by the first washing to obtain a filtrate; and The fifth step is to obtain a δ-phase perovskite crystal represented by the following chemical formula 3 by drying the above-mentioned filtrate. Chemical formula 1 AX Chemical formula 2 BX2 Chemical formula 3 ABX3 In the above Chemical Formula 1 and Chemical Formula 3, A is formamidine (FA), methylammonium (MA), FA x MA (1-x) (0 < X < 1) or N(R 1 )4 + , R 1 is a linear alkyl group with 1 to 5 carbon atoms, a branched alkyl group with 3 to 5 carbon atoms, a phenyl group, an alkylphenyl group or an alkoxyphenyl group In the above chemical formula 2 and chemical formula 3, B is Fe 2+ 、Co 2+ 、Ni 2+ , Cu 2+ Sn 2+ , Pb 2+ 、Bi 2+ ,Ge 2+ 、Ti 2+ 、Eu 2+ or Zr 2+ , X is I - , Cl - or Br - .

2. The method for preparing a δ-phase perovskite crystal according to claim 1, characterized in that: The solvent of the first step includes at least one selected from the group consisting of γ-butyrolactone, γ-valerolactone, α-angelica lactone, α-methylene-γ-butyrolactone, α-hydroxy-γ-butyrolactone and caprolactone.

3. The method for preparing a δ-phase perovskite crystal according to claim 1, characterized in that: In the first step, the reaction solution includes the organic anion precursor and the metal ion precursor in a molar ratio of 0.8-1.2:

1.

4. The method for preparing a δ-phase perovskite crystal according to claim 1, characterized in that: The anti-solvent includes at least one selected from chlorobenzene, toluene and xylene.

5. The method for preparing a δ-phase perovskite crystal according to claim 1, characterized in that: The amount of the anti-solvent added in the second step is 200 to 400 volume ratios relative to 100 volume ratios of the solvent used in the first step.

6. The method for preparing a δ-phase perovskite crystal according to claim 1, characterized in that: The poor solvent includes one or more nitrile solvents selected from acetonitrile, propionitrile and aminopropionitrile. The ether solvent includes at least one selected from diethyl ether, methyl t-butyl ether, diisopropyl ether and dibutyl ether.

7. The method for preparing a δ-phase perovskite crystal according to claim 1, characterized in that: The δ-phase perovskite crystals obtained in the fifth step have a yield of 75% or more and a purity of 99% or more.

8. A δ-phase perovskite crystal prepared by the method according to any one of claims 1 to 7, characterized in that: The above-mentioned δ-phase perovskite crystal is represented by the following chemical formula 3, Chemical formula 3 ABX3 In the above chemical formula 3, A is formamidine (FA), methylammonium (MA), FA x MA (1-x) (0 < X < 1) or N(R 1 )4 + , R 1 is a linear alkyl group with 1 to 5 carbon atoms, a branched alkyl group with 3 to 5 carbon atoms, phenyl, alkylphenyl or alkoxyphenyl, B is Fe 2+ , Co 2+ , Ni 2+ , Cu 2+ , Sn 2+ , Pb 2+ , Bi 2+ , Ge 2+ , Ti 2+ , Eu 2+ or Zr 2+ , X is I - , Cl - or Br - .